ECONOMIC GROWTH, LABOR INFORMALITY, EDUCATION, AND INCOME INEQUALITY: EVIDENCE FROM DYNAMIC PANEL DATA ACROSS INDONESIAN PROVINCES - Sintia Febrianty; Sayifullah Sayifullah (Adisam Publisher, 2026)
This study investigates the main determinants of income inequality across Indonesian provinces by employing dynamic panel data from 34 provinces over the 2015-2023 period. The study is motivated by the persistent disparity in regional income distribution despite continuous economic growth in Indonesia. Income inequality is proxied by the Gini ratio, while the explanatory variables consist of Gross Regional Domestic Product (GRDP), Provincial Minimum Wage (PMW), Labor Force Participation Rate (LFPR), percentage of informal workers, and Mean Years of Schooling (MYS). Considering the dynamic nature of inequality and the possibility of endogeneity among variables, the analysis applies a dynamic panel regression approach estimated using the System Generalized Method of Moments (System GMM). The empirical results indicate that lagged income inequality, GRDP, and the percentage of informal workers positively and significantly influence income inequality, implying that regional growth and labor market conditions remain uneven and less inclusive. Conversely, Mean Years of Schooling exerts a negative and significant effect, highlighting the important role of education in reducing inequality. Meanwhile, PMW and LFPR are found to have no significant impact on income inequality in Indonesia.